UNDERSTANDING THE LEVEL OF KNOWLEDGE AMONG NURSES ABOUT FIRE SAFETY IN TERTIARY CARE HOSPITAL LAHORE - SHAMAUN, R; NAZAR , A; MAHNOOR , M; TASNEEM, SS; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Fire safety in healthcare facilities is an important but frequently disregarded part of hospital administration and patient care. Despite substantial study on different aspects of healthcare delivery, there is still a significant gap in understanding and measuring fire safety knowledge and practices among healthcare personnel, particularly in Pakistan’s tertiary care facilities. Objective: The purpose of this study was to assess the degree of fire safety knowledge among medical personnel at a tertiary care hospital in Lahore, Pakistan, to identify any shortcomings that may affect their capacity to respond effectively in the event of a fire. Methods: A cross sectional quantitative descriptive study was conducted at Public Tertiary care hospital in Lahore involving 202 nurses. A customized questionnaire was administered to assess the participant’s fire safety knowledge, selected through successive sampling. Data analysis was performed using SPSS version 22.0, categorizing knowledge level as poor, average and good. Results: 85% of survey participants were aware of fire response procedures. However, only 15% knew the fire department contact numbers, and 25% were unaware that foam or water extinguishers are ineffective against grease fires. Additionally, a significant proportion of participants struggled to correctly identify different types of fire extinguishers (65%) and fire categories (50%). The finding underscore the importance of comprehensive fire safety training to address significant knowledge gaps. Conclusions: Healthcare institutions should develop comprehensive fire safety training programs that extend beyond basic emergency protocols. Regular fire drills and simulations should be held to check staff members’ understanding and reinforce fire safety procedures. Administrators should examine and update fire safety protocols on a regular basis to reflect new technology, legislation, and lessons learnt from previous events.